Administrative and legal supervision of the Veterinary Inspection over food safety in Poland – selected issues - Bonusiak, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Legal sciences, raising food safety as the subject of research, focus mainly on striving to ensure sufficiently effective legal regulations and the system of bodies controlling and supervising the food market that determine the correct health quality of food. One such body is the Veterinary Inspection. And while it focuses in its tasks mainly on the protection of animal health, it directly and indirectly affects the maintenance of food health requirements. Supervision exercised by the said Inspection plays an important role in ensuring a high level of protection of human life and health, and also protects the economic interests of the consumer. These two goals are basic. Additional objectives are protection of the reliability of commercial transactions, ensuring the free movement of food in the European Union, protection of animal health and living conditions and protection of the environment. They are of particular importance for determining acceptable limits of competences that can be entrusted to public administration bodies, including the said Inspection. The article presents the activities of the Veterinary Inspection to protect food safety and selected executive forms that it uses for this purpose. These types of entities are equipped with such forms of activity because they fulfill a protective function in the public administration system. However, this function implies the obligation to protect many different values desired individually, as well as maintain (ensure) objectively desired states of affairs, phenomena and processes.

Nauki prawne, podnosząc jako przedmiot badań bezpieczeństwo żywności, skupiają się głównie na dążeniu do zapewnienia odpowiednio skutecznych regulacji prawnych i systemu organów sprawujących kontrolę i nadzór nad rynkiem spożywczym, które determinują prawidłową jakość zdrowotną żywności. Jednym z takich organów jest Inspekcja Weterynaryjna. I o ile skupia się ona w swoich zadaniach głównie na ochronie zdrowia zwierząt, to jednak w sposób bezpośredni i pośredni wpływa na zachowanie wymagań bezpieczeństwa żywności. Sprawowany przez omawianą Inspekcję nadzór pełni istotną rolę w zapewnieniu wysokiego poziomu ochrony życia i zdrowia człowieka, a ponadto chroni interesy ekonomiczne konsumenta. Te dwa cele mają charakter podstawowy. Dodatkowymi celami są: ochrona rzetelności transakcji handlowych, zapewnienie swobodnego przepływu żywności w Unii Europejskiej, ochrona zdrowia i warunków życia zwierząt oraz ochrona środowiska. Mają one szczególne znaczenie dla wyznaczenia dopuszczalnych granic kompetencji, jakie mogą być powierzone organom administracji publicznej, w tym omawianej Inspekcji. Artykuł przedstawia działania Inspekcji Weterynaryjnej mające na celu ochronę bezpieczeństwa żywności oraz stosowane przez nią wybrane formy władcze o charakterze policyjnym. Tego rodzaju podmioty są wyposażone w takie formy działania, ponieważ pełnią w systemie administracji publicznej przede wszystkim funkcję ochronną. Natomiast z tej funkcji wynika powinność ochrony wielu zróżnicowanych wartości pożądanych jednostkowo, jak i utrzymania (zapewnienia) obiektywnie pożądanych stanów rzeczy, zjawisk i procesów.
Keywords: administration; supervision; food safety; veterinary inspection; consumer protection; administracja; nadzór; bezpieczeństwo żywności; inspekcja weterynaryjna; ochrona konsumenta